A Qualitative Inquiry into the Investment Decision Behaviour of the Malaysian Stock Market Investors. (1st August 2016) - Jaiyeoba, Haruna Babatunde; Haron, Razali
Abstract : Purpose: The main purpose of this study was to examine the investment decision behaviour of retail investors in Malaysia. Design/methodology/approach: The study adopted semi-structured interviews to solicit an understanding of six retail investors on investment decision behaviour in Malaysia. Content analysis technique was used to analyze the data and verbatim texts were applied in discussing the emergent themes. Findings: The findings indicate that retail investors in Malaysia are patriotic in nature and their investment decisions are based on feeling of comfort or convention rather than quantitative analysis. They rely so much on their findings rather than third party's views for making investment decisions. They were influenced by the psychological biases as they herd on the information. Challenges are solved through experience and they believe that proper understanding of the financial and economic settings of the country can enhance better investment decision making. Research limitations/implications: A more detailed investigation on the investors' behaviour with more samples may expand our understanding of this issue. Future studies need to examine the investment decision behaviour with more samples. Practical implications: Firstly, it will prepare hit and run investors to be more ready to remain in the market and improve their skills on how to make sound investment decisions. Secondly, it helps the investors to know that knowledge of traditional finance theory is not sufficient to excel in stock market and hence, they need to know more about behavioural finance. Thirdly, investors are exposed to various reasons why investment decisions deviate from expected and different means of solving the challenges faced in making investment decision within the Malaysian context. Fourthly, investors are reminded that understanding the financial settings before investing is essential. Finally, policy makers in stock market are able to understand the retail investors' behaviour. Originality/value: This study examines the experience and prospect to remain as stock market investors, their priorities in selecting the right company for investment purposes, the kind of information seeking from third parties, the challenges faced by them and other important considerations in investment decisions. These have never been examined together in this way in investigation of retail investors' investment behaviour.